2016
DOI: 10.1007/s10290-016-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

Are workers more vulnerable in tradable industries?

Abstract: Reduced trade barriers and lower costs of transportation and information have meant that a growing part of the economy has been exposed to international trade. In particular, this is the case in the service sector. We divide the service sector into a tradable and a non-tradable part using an approach to identify tradable industries utilizing a measure of regional concentration of production. We examine whether the probability of displacement is higher and income losses after displacement greater for workers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Construction, for example, is tradeable in theory but in practice its activities concentrate within countries or even regions. Our classifications broadly correspond to those from studies on Sweden and France, which use measures of geographical concentration to identify tradeable industries (Eliasson and Hansson, 2016;Frocrain and Giraud, 2017). The distinction between the market and non-market sectors may be ambiguous due to (quasi-)privatisations (such as in electricity and gas) and parallelly operating private and public services (such as in health care).…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction, for example, is tradeable in theory but in practice its activities concentrate within countries or even regions. Our classifications broadly correspond to those from studies on Sweden and France, which use measures of geographical concentration to identify tradeable industries (Eliasson and Hansson, 2016;Frocrain and Giraud, 2017). The distinction between the market and non-market sectors may be ambiguous due to (quasi-)privatisations (such as in electricity and gas) and parallelly operating private and public services (such as in health care).…”
Section: Independent Variablesmentioning
confidence: 99%
“…They found no relation between the sector’s exposure to globalisation and career destabilisation but found that careers were more complex in both particularly low- and high-growth sectors. Differentiating between sectors of tradeable goods and services on the one hand and non-tradeable services on the other, Eliasson and Hansson (2016) pointed out that in Sweden, workers in sectors more open to globalisation were more vulnerable to unemployment. A sector that is typically shielded from career destabilisation is the public sector (Biemann et al, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Early studies by Amiti and Wei (2005, 2006) based on sector‐level data for, respectively, UK and US manufacturing find a small negative or no effect of service offshoring on labour demand in the US, but a small positive effect in the UK. Eliasson and Hansson (2016) use linked employer–employee data for Sweden to investigate whether there are differences in the probability of displacement and in the income losses after displacement for workers in manufacturing and tradeable services vis‐à‐vis non‐tradeable services. Their focus is on large mass dismissal and establishment closure.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Yet recent advances in information and communication technologies have increased the tradability of a great number of products and especially services, providing employment opportunities and risks. Surprisingly, only very few studies - Jensen and Kletzer (2005), Hlatshwayo and Spence (2014) for the United States, and Eliasson et al (2012), Eliasson and Hansson (2016) for Sweden -have done a detailed analysis of tradable and non-tradable employment. We contribute to this recent literature and to the debate on the effects of increased globalization on the employment structure of our economies by analyzing employment, wages, skills, and labor productivity patterns across tradable and non-tradable industries in France from 1999 to 2015.…”
Section: The Evolution Of Tradable and Non-tradable Employment: Evidementioning
confidence: 99%